2021
DOI: 10.1123/ijsnem.2020-0211
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Nonpharmacological Strategies in the Treatment of Relative Energy Deficiency in Sport

Abstract: Relative energy deficiency in sport (RED-S) can result in negative health and performance outcomes in both male and female athletes. The underlying etiology of RED-S is low energy availability (LEA), which occurs when there is insufficient dietary energy intake to meet exercise energy expenditure, corrected for fat-free mass, leaving inadequate energy available to ensure homeostasis and adequate energy turnover (optimize normal bodily functions to positively impact health), but also optimizing recovery, traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 75 publications
0
31
0
4
Order By: Relevance
“…While the obvious strategy for correcting LEA is to focus on increasing energy intake or reducing activity energy expenditure [ 150 ], as discussed in the current review, underlying issues such as disordered eating tendencies or body image concerns may contribute to the issue of LEA and therefore warrant attention. As such, early educational interventions will likely be instrumental in helping improve any behavioral tendencies (e.g., energy restriction, exercise dependance, etc.)…”
Section: Practical Recommendations and Future Directionsmentioning
confidence: 99%
“…While the obvious strategy for correcting LEA is to focus on increasing energy intake or reducing activity energy expenditure [ 150 ], as discussed in the current review, underlying issues such as disordered eating tendencies or body image concerns may contribute to the issue of LEA and therefore warrant attention. As such, early educational interventions will likely be instrumental in helping improve any behavioral tendencies (e.g., energy restriction, exercise dependance, etc.)…”
Section: Practical Recommendations and Future Directionsmentioning
confidence: 99%
“…Resumption of regular periods is an encouraging clinical sign, nevertheless it is not possible to be certain that full hormone network function has been restored. Having quantified detail about the effect of non-pharmacological strategies on recovery of menstrual cycle hormone function would be very valuable[19]. This study found that modelling all the menstrual cycle hormones over an entire cycle for an individual female proved a personalised, practical and sensitive clinical tool to indirectly monitoring energy availability.…”
Section: Discussionmentioning
confidence: 99%
“…A primary concern regarding Kuikman et al's (2021) review stems from the way in which content was framed and presented by the authors, wherein foundational research regarding the effects of EA, as it relates to menstrual and bone health, was omitted, and the purposes of previous investigations were rebranded to fit RED-S when the Triad was, in fact, the focus of the research. We understand that there has been historic disagreements between Triad and RED-S researchers (De Souza et al, 2014b;Mountjoy et al, 2015;Williams et al, 2019), but the complete absence of reference to the Triad in this manuscript is not accurate (Kuikman et al, 2021). Notably, every study cited within the "Improving EA" section (Cialdella-Kam et al, 2014;Dueck et al, 1996;Kopp-Woodroffe et al, 1999;Lagowska et al, 2014b;Mallinson et al, 2013), in addition to the other studies that were not referenced (Arends et al, 2012;Lagowska et al, 2014a), was designed to assess whether improved energetic status (i.e., increased EA) specifically leads to recovery of menstrual function and/or improved bone health in exercising women with menstrual disturbances; that is, recovery from the Triad (De Souza et al, 2014a;Nattiv et al, 2007).…”
mentioning
confidence: 87%
“…The Pennsylvania State University aaa A recently published review by Kuikman et al (2021) focused on potential nonpharmacological treatments for relative energy deficiency in sport (RED-S) and aimed to highlight (a) interventions that improved energy availability (EA), (b) interventions that targeted factors known to exacerbate and/or independently affect the health outcomes of low EA (e.g., carbohydrate availability, fiber intake, and micronutrients), and (c) nonnutritional adjunct therapies (resistance training and cognitive behavioral therapy). Although we may be early career researchers who do not yet have decades of experience in this field, we do still have an appreciation for evidence-based research and the many steps that are necessary to accumulate evidence in support of a developing scientific model.…”
mentioning
confidence: 99%